Synthesis and Spectral Studies on Cobalt(II), Nickel(II), Copper(II), Palladium(II), Platinum(II, IV), Zinc(II), Cadmium(II) and Mercury(II) Complexes of(1, 2-diaminoethane-N,N'-bis(2- butylidine-3 onedioxime) - Al-Jeboori, M. J.; Abdul Rahman, A. S. A.; Atia, S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The synthesis of [1,2-diaminoethane-N,N'-bis(2-butylidine-3- onedioxime)] [II2L] and its cobalt(II), nickel(II), copper(II), palladium(II), platinum(II, IV), zinc(II), cadmium(II) and mercury(II) complexes is reported. The compounds were characterised by elemental analyses, spectroscopic methods [I.R, UV-Vis, ('H NMR. and EI mass for H2L)], molar conductivities, magnetic moments. I.R. spectra show that (H2L) behaves as a neutral or mononegative ligand depending on the nature of the metal ions. The molar conductance of the complexes in (DMSO) is commensurate with their ionic character. On the basis of the above measurements, a square planar geometry is proposed for NOD, Pd(II), and Pt(II) complexes, and an octahedr-al structure with trans dichloro ligands at the axial position is proposed for Pt(IV) complex. While [Cu(II) and Co(II)] and [Zn(II), Cd(II) and Hg(II)] adopted a distorted tetrahedral and tetrahedral geometry, respectively.